Update: Biological and chemical aspects of Senna spectabilis - Selegato, Denise M. [UNESP]; Monteiro, Afif F. [UNESP]; Vieira, Natï¿½lia C. [UNESP]; Cardoso, Patrï¿½cia [UNESP]; Pavani, Victor D. [UNESP]; Bolzani, Vanderlan S. [UNESP]; Castro-Gamboa, Ian [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2017)
Senna spectabilis (syn Cassia spectabilis) is one of the most important species within the Fabaceae family, natively found in Central and South America, as well as parts of Asia and Africa. Due to the extensive geographical distribution, this fast-growing tree produces a wide variety of bioactive secondary metabolites, being of special interest for chemical and pharmacological studies. Phytochemical investigations have shown that S. spectabilis produces over 40 constituents from different biosynthetic pathways, including piperidine alkaloids, pentacyclic terpenoids and anthraquinones, displaying antiproliferative, antitumoral and antifungal activities. Moreover, studies have also been conducted to identify endophytic and rizhospheric microorganisms associated to S. spectabilis and their chemical composition, enabling further elucidation of cadinane sesquiterpenoids, cytochalasins, depsipeptides and dibenzopirones. This review aims to provide an updated summary of the main features of S. spectabilis, compiling all currently available information on the chemical and pharmacological composition of its parts and its associated microorganisms.
Keywords: Associated microorganisms; Biological activity; Bioprospection; Phytochemistry; Senna spectabilis